Complex of Measures Aimed at Prevention of Ebola Virus Disease Importation and Transmission, Performed within the Frames of Sanitary Protection of the Territories of the Russian Federation - A. Yu. Popova; A. E. Shiyanova; E. B. Ezhlova; Yu. V. Demina; N. D. Pakskina; O. V. Kedrova; L. N. Dmitrieva; I. G. Karnaukhov (Проблемы особо опасных инфекций, 2015)
An estimated scope of measures, aimed at the prevention of Ebola virus disease importation and transmission in the territory of the Russian Federation, targets the maximum level of hazard to the population. It has a complex interagency character, whereby the Federal service for surveillance in the sphere of consumers rights protection and human welfare functions as coordinator and principal executing agency. The measures affect the following areas: regulatory compliance and methodological support, sanitary-quarantine control reinforcement at the entry points on the state border of the Russian Federation, strengthening of anti-epidemic preparedness of the Rospotrebnadzor and public healthcare institutions and authorities, including operational preparedness of the laboratory facilities, information support within the framework of epidemiological surveillance, and involvement in the activities under the international collaboration for epidemic response and control. Practices have been completed as regards series of actions conducted from the time of the case identification and further on; evacuation of the infected and suspected individuals, procedures for sanitary disinfection, interventions in the relation to contact persons, and readiness for anti-epidemic measures performance.